2023
DOI: 10.3389/fonc.2023.1288504
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis: emerging biomarkers and potential therapeutics in cancers

Min Wang,
Lianwen Zheng,
Shuai Ma
et al.

Abstract: The sustenance of human life activities depends on copper, which also serves as a crucial factor for vital enzymes. Under typical circumstances, active homeostatic mechanisms keep the intracellular copper ion concentration low. Excess copper ions cause excessive cellular respiration, which causes cytotoxicity and cell death as levels steadily rise above a threshold. It is a novel cell death that depends on mitochondrial respiration, copper ions, and regulation. Cuproptosis is now understood to play a role in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…These studies have revealed the significant role of cuproptosis-related genes in signaling pathways associated with tumorigenesis [ 23 ]. For treating early lung cancer, cuproptosis could potentially be a valuable therapeutic approach [ 39 ]. Research into the role of cuproptosis in the treatment of early-stage lung cancer has focused on understanding the mechanisms of this form of cell death and developing prognostic models based on cuproptosis-related biomarkers [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have revealed the significant role of cuproptosis-related genes in signaling pathways associated with tumorigenesis [ 23 ]. For treating early lung cancer, cuproptosis could potentially be a valuable therapeutic approach [ 39 ]. Research into the role of cuproptosis in the treatment of early-stage lung cancer has focused on understanding the mechanisms of this form of cell death and developing prognostic models based on cuproptosis-related biomarkers [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process promotes tumour growth [32]. Furthermore, the amassment of this ion has been found to correlate with cancer angiogenesis [27]. It is showed that copper exhibits precise spatial regulation, moving from perinuclear regions of the cell towards the ends of extending filopodia and traversing the cell membrane into the extracellular space during angiogenic processes [36].…”
Section: Copper In Cancermentioning
confidence: 99%
“…It engages in various biological processes, such as lipid metabolism, energy regulation, and the synthesis of neurotransmi ers [26]. In normal conditions, effective homeostatic mechanisms maintain a low concentration of intracellular copper ions [27]. However, an imbalance in cellular metal ion levels, whether in excess or deficiency, can be equally detrimental, as it may lead to an intensified rise in oxidative stress in both scenarios [28].…”
Section: Copper's Biological Rolementioning
confidence: 99%
See 2 more Smart Citations